Efektivitas Teknik Assertive Training Terhadap Perilaku Toxic Friendship Pada Siswa SMP Plus Abdul Aziz Jember - Fitriya, Lailatul; Hikmatul Maghfiroh, Nasruliyah; Sukmawati, Bhennita (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
Toxic friendship refers to unhealthy peer relationships that can negatively affect adolescents emotionally, psychologically, and socially. Such relationships may reduce self-confidence, hinder social development, and trigger prolonged emotional stress. This study aims to examine the effectiveness of Assertive Training in reducing toxic friendship behavior among students at SMP Plus Abdul Aziz Jember. A quantitative approach with a quasi-experimental design using a pre-test–post-test control group was employed. The sample consisted of 12 students selected through purposive sampling, divided into an experimental group and a control group. The experimental group received Assertive Training as part of a Cognitive Behavioral Therapy (CBT) intervention, while the control group did not receive any treatment. Data analysis using a paired sample t-test revealed a significant decrease in toxic friendship levels in the experimental group, indicated by a shift in scores from high to low (p = 0.000), whereas the control group showed no significant change. The novelty of this study lies in applying CBT-based Assertive Training specifically to address toxic friendship among junior high school students. These findings provide practical implications for guidance and counseling services, supporting students in developing healthier, more open, and assertive peer relationships. Keywords: Assertive Training; Toxic,Friendship